The study of religion in Sweden: past, present and future - Bogdan, Henrik; Larsson, Göran (Bloomsbury Academic, 2024)
"Examines the historical development of the study of religions in Sweden - often called the most secularized country in the world - as well as the impact of Swedish scholarship internationally"--